Hebt das Emissionshandelssystem die Einsparungen des Ökostromausbaus auf? - Ralf-M. Marquardt (Wirtschaftsdienst, 2016)
Die deutsche Energiepolitik verfolgt zwei wesentliche Ziele, zum einen die Abkehr vom Atomstrom (Energiewende), zum anderen den Ausbau erneuerbarer Energien, um für das Klima gefährliche Treibhausgase einzusparen. Dabei kommen unterschiedliche Instrumente zum Einsatz, die sich teilweise gegenseitig behindern. Der Autor zeigt die Wechselwirkungen des Erneuerbare-Energien-Gesetzes und des europäischen Emissionshandelssystems auf. – – Notwithstanding the increasing costs of the expansion of renewable energies, the Energy Transition in Germany still enjoys a high level of acceptance. Mainly this is due to the wide-spread perception that a non-fossil based production of electricity will automatically reduce greenhouse gas emissions. While this is true regarding the direct displacement effect, this paper points out that it is not that clear in a holistic view. Considering the interaction between the expansion of renewables and the EU-Emission-Trading-System, indirect price effects on carbon prices occur, which might counteract or even dominate the direct displacement effect. In order to enhance the greenhouse gas effectiveness, an automatic cut of the emission cap by the direct displacement effect should be considered.
Keywords: Q48; Q54; Q58; 330; Förderung erneuerbarer Energien; Emissionshandel; Wirkungsanalyse; Szenariotechnik; Deutschland